美德倫理的主體性式微及公共健康倫理的價值重塑: The Decline of Subjectivity in Virtue Ethics and the Reshaping of the Value of Public Health Ethics - YE, Chenlu; LIU, Bojing (International Journal of Chinese & Comparative Philosophy of Medicine, 2024)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. For more than half a century, the virtue ethics framework has been a core element of modern ethical systems. However, in the post-pandemic era, scientific and technological perspectives related to artificial intelligence and generative artificial intelligence are quietly “replacing” virtue as an ethical subject, and “human” and “virtue” are themselves being understood as having “digital” and “antimoral inclinations”. Given the decline of interest in the subjectivity that is characteristic of virtue ethics, the importance of re-interpreting its subjective value and returning to traditional virtue theory to achieve the modernisation of virtue ethics is self-evident.